A nursing process model for a hospital - systematic literature review - Ana Guimarães; Isabel CF da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
To implement a model of nursing process in hospital for high complexity clients a systematic literature review will be done ti identify best practices that can be utilized.